Some aspects of the industrial capital market in Ireland - Murray, C. H. (Statistical and Social Inquiry Society of Ireland, 1960)
Industry in Ireland is financed in a variety of ways?by public issues, retained profits and depreciation allowances, trade credit, loans from commercial banks, the Industrial Credit Company Ltd. and hire-purchase concerns, government grants, etc. This paper is not concerned with the broader aspects of investment in Irish industry. There is need for such a review but it is not attempted in the present paper, which has the more limited objective of bringing together some facts relating to investment by the public in Irish industry, and of indicating?largely by reference to experience elsewhere?what might be done to improve the institutional and other facilities for this investment. This means that a large part of the remarks which follow will relate to the Stock Exchanges and to their functions and potentialities in channelling Irish savings into Irish industry.
Read before the Society, 4 March 1960
Keywords: Industrial capital market of Ireland; Dublin Stock Exchange; Corporate financing of Irish companies; 314.15